2020
DOI: 10.1101/2020.04.21.053991
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An opaque cell-specific expression program of secreted proteases and transporters allows cell-type cooperation inCandida albicans

Abstract: An unusual feature of the opportunistic pathogen C. albicans is its ability to stochastically switch between two distinct, heritable cell types called white and opaque. Here, we show that only opaque cells, in response to environmental signals, massively up-regulate a specific group of secreted proteases and peptide transporters, allowing exceptionally efficient use of proteins as sources of nitrogen. We identify the specific proteases (members of the secreted aspartyl protease (SAP) family) needed for opaque … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 99 publications
(122 reference statements)
0
2
0
Order By: Relevance
“…Ten secreted aspartic proteases (Saps) have been identified in C. albicans, which are encoded by the SAP genes (SAP1 to SAP10) [26] and associated with bovine serum albumin (BSA) utilisation [27]. It has been demonstrated that Saps are involved in protection from host defence proteins, biofilm formation and adhesion, among other functions [27]. Many studies have demonstrated that the Rpd3 HDAC plays a critical role in virulence [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten secreted aspartic proteases (Saps) have been identified in C. albicans, which are encoded by the SAP genes (SAP1 to SAP10) [26] and associated with bovine serum albumin (BSA) utilisation [27]. It has been demonstrated that Saps are involved in protection from host defence proteins, biofilm formation and adhesion, among other functions [27]. Many studies have demonstrated that the Rpd3 HDAC plays a critical role in virulence [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Many virulence factors provide important functions required for the pathogenesis of C. albicans , such as morphogenesis (the transition between yeast and hyphae), white (W)/opaque (O) switching [24], secreted aspartic proteases (Saps) and adhesins [25]. Ten secreted aspartic proteases (Saps) have been identified in C. albicans , which are encoded by the SAP genes ( SAP1 to SAP10 ) [26] and associated with bovine serum albumin (BSA) utilisation [27]. It has been demonstrated that Saps are involved in protection from host defence proteins, biofilm formation and adhesion, among other functions [27].…”
Section: Introductionmentioning
confidence: 99%